2020
DOI: 10.2320/matertrans.mt-m2020047
|View full text |Cite
|
Sign up to set email alerts
|

Pressure–Composition Phase Diagram of Fe–Ni Alloy

Abstract: We investigated the structural phase transitions of FeNi alloys under hydrostatic pressure conditions at 298 K by examining the X-ray diffraction patterns of polycrystalline samples with Ni contents of 5%31.6%, and pressurecomposition phase diagram was established for the pressure range of 015 GPa. The diagram comprised three structural phases: bcc, fcc, and hcp, and these all coexisted in 25% Ni at 11 GPa during compression and in 23% Ni at 7 GPa during decompression. During both processes, low-and high-press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…A 200 μm hole bored in a work hardened rhenium gasket ( h = 80 μm) was loaded with Fe 84 Ni 16 together with Si gel and rubies, identical to the SIRM experiments; rubies were placed on the side with the solid, nonperforated diamond. We used Fe 84 Ni 16 due to its lower bcc‐hcp transition pressure (∼9–10 GPa, Huang et al., 1988 and ∼12 GPa, Akahama et al., 2020) than that for Fe 100 Ni 0 , as the highest pressure attainable by the partially perforated diamond was uncertain. We first measured the XAFS and XMCD at the K‐edge of Fe in the diamond cell at ambient P and T as a function of applied field strength in order to know the field intensity required to attain saturation (Figure 4a).…”
Section: Experimental Procedures and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A 200 μm hole bored in a work hardened rhenium gasket ( h = 80 μm) was loaded with Fe 84 Ni 16 together with Si gel and rubies, identical to the SIRM experiments; rubies were placed on the side with the solid, nonperforated diamond. We used Fe 84 Ni 16 due to its lower bcc‐hcp transition pressure (∼9–10 GPa, Huang et al., 1988 and ∼12 GPa, Akahama et al., 2020) than that for Fe 100 Ni 0 , as the highest pressure attainable by the partially perforated diamond was uncertain. We first measured the XAFS and XMCD at the K‐edge of Fe in the diamond cell at ambient P and T as a function of applied field strength in order to know the field intensity required to attain saturation (Figure 4a).…”
Section: Experimental Procedures and Resultsmentioning
confidence: 99%
“…Huang et al (1988) found that the bcc to hcp phase transition decreases in pressure with increasing Ni, being ~11 GPa and ~8 GPa for Ni concentrations of 10% and 25% respectively. Using a monochromatic synchrotron radiation X-ray source, Akahama et al (2020)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Принято считать, что структура ЖНС представляет собой γ-твердый раствор легирующих элементов в никелевой матрице (геометрическая модель -ГЦК-структура [13]) и дисперсных выделений γ'-фазы на основе Ni 3 Al при очень близких периодах их кристаллических решеток, дающих взаимное несоответствие («мисфит») не выше 0.5 % и результирующим параметром ячейки решетки, рассчитывающимся как арифметическое среднее параметров решеток γ-и γ'-фаз. Этот фактор необходимо в той или иной степени учесть при расчетах плотности ЖНС.…”
Section: структура и подходы к оценке плотности жнсunclassified